Difficulties of Differential Diagnosis of Colon Diseases in the Infectious Practice - L. N. Mazankova; T. A. Chebotareva; E. I. Aliyevа; M. I. Pykov; E. I. Makarova; E. G. Moreva (LLC "Diagnostics and Vaccines", 2016)
The paper presents an algorithm of differential diagnosis of inflammatory bowel disease with infectious and parasitic diseases, described the case of diagnosis of Crohn's disease in the infectious department general hospital with a sequence of examinations of the child in the gastroenterological department, showing features of the development and course of Crohn's disease in a child 16 years with the debut on the background intestinal infections.